2013
DOI: 10.1016/s0254-6272(14)60022-4
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of constipation-predominant irritable bowel syndrome by focusing on the liver in terms of Traditional Chinese Medicine: a meta-analysis

Abstract: Compared with Western Medicine, the treatment of IBS-C based on the liver is significantly better but the results must be treated with caution because publication bias was recorded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 4 publications
0
17
0
3
Order By: Relevance
“…TCM: Eine MA 646 (19 RCTs, N = 1510) zum RDS-Subtyp Obstipation verglich TCM mit Fokus auf der Leber mit westlicher Schulmedizin hinsichtlich eines globalen Wirksamkeitsmaßes und kommt zu dem Ergebnis, dass TCM wirksamer ist. Die Studienqualität der inkludierten RCTs ist allerdings sehr gering und ein Publikationsbias wurde bestätigt, weswegen diese Ergebnisse kaum zu verwenden sind.…”
Section: Teil IV – Allgemeine Therapieverfahrenunclassified
See 1 more Smart Citation
“…TCM: Eine MA 646 (19 RCTs, N = 1510) zum RDS-Subtyp Obstipation verglich TCM mit Fokus auf der Leber mit westlicher Schulmedizin hinsichtlich eines globalen Wirksamkeitsmaßes und kommt zu dem Ergebnis, dass TCM wirksamer ist. Die Studienqualität der inkludierten RCTs ist allerdings sehr gering und ein Publikationsbias wurde bestätigt, weswegen diese Ergebnisse kaum zu verwenden sind.…”
Section: Teil IV – Allgemeine Therapieverfahrenunclassified
“…Schmerzen Blähungen Obstipation Diarrhoe Globaler RDS-Symptomkomplex 1. Ganzheitliche Medizinsysteme TCM [645][646][647] Akupunktur [641][642][643][644] x…”
Section: Interventionunclassified
“…We identified 212 studies in the six databases. After removing duplications and excluding studies that did not meet the inclusion criteria by reading the titles, abstracts, and full texts, 17 SRs ( Spanier et al, 2003 ; Bian et al, 2006 ; Liu et al, 2006 ; Shi et al, 2008 ; Li et al, 2013 , 2015 , 2017 ; Zhang et al, 2014 ; Xiao Y. et al, 2015 ; Zhu et al, 2016 ; Dai et al, 2018 ; Zhou et al, 2019 ; Bu et al, 2020 ; Wang et al, 2020 ; Tan et al, 2020 ; Yao et al, 2021 ; Zheng et al, 2021 ) were found to be eligible for this overview. Among these SRs, 16 SRs and an overview of SRs ( Zhang et al, 2014 ) were included.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 18 studies (22.2%) [ 33 , 35 , 37 , 41 , 42 , 49 , 62 , 65 , 79 , 81 , 83 , 86 – 88 , 91 , 99 , 102 , 107 ] reporting outcomes on adverse events, seven studies [ 37 , 49 , 65 , 79 , 83 , 88 , 91 ] found no adverse events, and four studies [ 35 , 62 , 81 , 87 ] reported patients having slight bleeding when the needle was withdrawn. The remaining seven studies reported adverse events from eye acupuncture as well as events from other interventions during the treatment, which are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%